2006
DOI: 10.1158/1535-7163.mct-06-0134
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of alexidine dihydrochloride as an apoptosis-promoting anticancer agent

Abstract: Despite advances in surgery, radiation, and chemotherapy, novel therapeutics are needed for head and neck cancer treatment. The objective of this current study was to evaluate alexidine dihydrochloride as a novel compound lead for head and neck cancers. Using a tetrazolium-based assay, the dose required to reduce cell viability by 50% (ED 50 ) was found to be f1.8 Mmol/L in FaDu (human hypopharyngeal squamous cancer) and f2.6 Mmol/L in C666-1 (human undifferentiated nasopharyngeal cancer) cells. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 27 publications
4
42
0
3
Order By: Relevance
“…ALX has disinfection efficacy against all bacteria and fungi tested by contact lens disinfection standard (23). A recent study has suggested the potential use of ALX as a novel anticancer compound (36). Although ALX has less effect on plaque accumulation and shorter residual antibacterial activity than CHX (37), it might be valuable for endodontic irrigation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…ALX has disinfection efficacy against all bacteria and fungi tested by contact lens disinfection standard (23). A recent study has suggested the potential use of ALX as a novel anticancer compound (36). Although ALX has less effect on plaque accumulation and shorter residual antibacterial activity than CHX (37), it might be valuable for endodontic irrigation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Although tests for inhibition of this phospholipase in cells were not carried out, this raises the possibility that some cross-reactivity of the compound with phospholipases in mammalian cells could exist. In terms of toxicity to mammalian cells, one study (Yip et al, 2006) has suggested that alexidine dihydrochloride at low micromolar concentrations may be cytotoxic to some cancer cells but less toxic to untransformed cells. At the concentrations used in our experiments with primary pancreatic islet cells, we did not observe significant cytotoxicity while still observing a significant and PTPMT1-selective effect of alexidine on insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As the role of PTPMT1 had previously been studied in the pancreatic ␤-cell, and genetic perturbation had been shown to affect insulin secretion, we used this system as our model. Because lipophilic dications have also been reported to show cellular toxicity at high concentrations (Severina et al, 2007) and most previous studies of alexidine dihydrochloride have focused on its antimicrobial and cytotoxic effects (Gilbert and Moore, 2005;Yip et al, 2006), we first ensured that the assays were performed at concentrations that did not affect cell viability. Through use of a cell membrane integrity-based cytotoxicity assay, we found that alexidine dihydrochloride did not significantly affect membrane permeability and viability of the cells of pancreatic islets at concentrations up to 4 M, hence this was the maximum concentration used in the assays.…”
Section: Alexidine Dihydrochloride Stimulates Insulin Secretion From mentioning
confidence: 99%
“…Polymeric drug delivery systems such as liposomes, polymeric micelles, and nano hydrogels were used in successful controlled delivery but they also suffered in one or more physicochemical aspects, like stability and durability these makes to them to release the payloads unexpectedly in a burst release manner [9]. MSNs not only proved themselves as effective carriers for controlled drug delivery [12][13][14][15][16][17] but also they were effectively used in bio-signal probing tools [18][19][20] and as biomarker supporter [21] as imaging and sensing tool.…”
Section: Introductionmentioning
confidence: 99%